A novel colorimetric and ratiometric fluorescent probe for targeted detection of hypochlorous acid based on HClO-mediated anthracene-hydrazone to anthracene-triazole transformation. Issue 32 (30th July 2019) - Jiang, Chen; Yao, Yuewei; Kong, Chuilian; Du, Jiaqi; Meng, Jingjing; Yao, Cheng
Abstract : An anthracene-based fluorescence probeB-ClO that exhibited excellent selectivity and sensitivity for colorimetric and ratiometric detection of ClO − in 80% aqueous DMF solution has been designed and developed. Abstract : A novel naked-eye colorimetric and ratiometric fluorescent probe (B-ClO ) was transformed from anthracene-hydrazone to anthracene-triazole based on a HClO-mediated cyclization reaction with an F 434 nm / F 570 nm ratio in quantitative response to HClO. TheB-ClO probe exhibited high sensitivity (limit of detection of 14 nM) and a fast response time to ClO − over other competing species as well as across a wide pH range. Study of the sensing mechanism supported a HClO-mediated cyclization reaction in which 1, 2, 4-triazole forms via HClO and a hydrazone derivative, with excellent photophysical properties. Such a probe was used asB-ClO test strips andB-ClO silica materials to monitor HClO in the environment, exhibiting excellent solid properties.